Studi Teologis - Historigrafis Kisah Para Rasul 1-2 sebagai Dasar Membangun Spirit Teologi Pentakosta - Maahury, Simon Moshe; Wijoyo, Sigit (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2023)
The reinterpretation of Pentecostal theology has generated criticism that tends towards anti-Pentecostal theological thinking. An examination of the historical context and biblical foundations that form the roots of Pentecostal theology is essential for understanding the historical context and theological messages embedded in it. This paper seeks to examine the Acts chapter 1-2 from the perspective of historiography and theological documents. The research aims to explore the theological values of the Acts chapter 1-2 documents constructed based on historical narratives. Through historiographical and theological approaches, the Pentecostal events recorded in Acts of the Apostles 1-2 are elaborated in-depth. According to the researcher's findings, it is revealed that the Pentecostal events in Acts chapter 1-2 provide impetus for Christians to engage in God's mission, offering a spirit of God's presence and a Christocentric life. The findings in this research also challenge the criticism that Pentecostal theology solely emphasizes spiritual restoration of a personal nature. The presence of Pentecostal theology complements the unity of the body of Christ and enriches the values of Christian theology.Reinterpretasi terhadap teologi Pentakosta menimbulkan kritik yang mengarahkan pada pemikiran anti teologi Pentakosta. Adanya kajian sejarah serta landasan biblika yang menjadi akar teologi Pentakosta sangat diperlukan untuk mengetahui konteks kesejarahan dan pesan teologis yang disematkan. Tulisan ini berupaya untuk meneropong dokumen Kisah Para Rasul 1-2 dengan dari sudut pandang historiografi dan dokumen teologis. Riset ini bertujuan untuk mengeksplorasi nilai-nilai teologis dokumen Kisah Para Rasul yang dibangun berdasarkan paparan sejarah. Melalui pendekatan historiografi dan teologis, peristiwa catatan peristiwa Pentakosta dalam Kisah Para Rasul 1-2 dielaborasi secara mendalam. Dalam temuan peneliti, terungkap bahwa peristiwa Pentakosta dalam Kisah Para Rasul 1-2 memberikan dorongan bagi orang Kristen bergiat pada misi Allah, memberikan spirit kehadiran Allah serta kehidupan yang Kristosentis. Temuan dalam riset ini juga menyanggah adanya kritik bahwa teologi Pentakosta hanya menekankan pada restorasi rohani yang hanya bersifat personal. Hadirnya teologi Pentakosta melengkapi justru kesatuan tubuh Kristus dan memperkaya nilai teologi Kristen.